(untitled) (World of finance, 2021)
Introduction. Gold price has being demonstrating stable tendency to rise during recent time. Stronger geopolitical tensions support the view that that international political economy factors may play a role driving gold price. In the same time post-crisis global economic uncertainty and global expansion of liquidity may affect gold price by itself. The purpose of the article is to find which gold price factor is the most important taking into account assumption that global macrofinancial conditions affect assets prices yet the real economy. Results. We consider competitive approaches on gold price factors: international political economy, safe haven effect, hedging against monetary shocks, assets with negative beta. Gold reserves accumulation may support ideas that reflected in economic literature about gold price factors. In the same time, fraction of gold in global exchange reserves didn’t change substantially during recent time. For empirical test the four groups of factors were chosen. Each of them are proxy for geopolitical tensions, global economic policy uncertainty, global exchange reserves accumulation, monetary / financial conditions in US. It is found that factors of international political economy are not valid. The most important factors are global economic policy uncertainty and expansion of global liquidity in the form of low long-term US interest rates and global exchange reserves accumulation. Conclusions. Gold price drivers are on the global macrofinancial conditions side. The role of international political economy factors is overvalued.